Array comparative genomic hybridisation on first polar bodies suggests that non-disjunction is not the predominant mechanism leading to aneuploidy in humans. Issue 7 (26th May 2011) - Gabriel, A S; Thornhill, A R; Ottolini, C S; Gordon, A; Brown, A P C; Taylor, J; Bennett, K; Handyside, A; Griffin, D K
Abstract : Introduction: Aneuploidy (the presence of extra or missing chromosomes) arises primarily through chromosome segregation errors in the oocyte at meiosis I but the details of mechanism by which such errors occur in humans are the subject of some debate. It is generally believed that aneuploidy arises primarily as a result of segregation of a whole chromosome to the same pole as its homologue (non-disjunction). Nonetheless, classical cytogenetic studies suggest that this model does not fully account for the patterns observed in human oocytes. An alternative model (precocious separation of sister chromatids) has thus been proposed, but recurring criticism of this model purports that technical issues may have led to interpretation errors. Materials and methods: Array comparative genomic hybridisation (aCGH) was used on 164 human first polar bodies to distinguish between whole chromosome (non-disjunction) and chromatid (precocious separation) errors. Results: Single chromatid errors were over 11 times more common than whole chromosome errors, consistent with prior classical cytogenetic and fluorescence in situ hybridisation (FISH) studies. Discussion: The received wisdom that non-disjunction is the primary mechanism leading to human aneuploidy should be reconsidered.